Analysis of the fire hazard posed by petrol stations in Stellenbosch and the extent to which planning acknowledges risk - Qonono, Kwanele (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPhil)--Stellenbosch University, 2019.